Perkembangan Perbankkan Syariah di era Ekonomi Digital - Zulfa Khoiriah; M. Irwan Padli Nasution (Economic Reviews Journal, 2023)
Digital transformation is not just a move from traditional banking to a digital world but rather an important change in the way banks interact and satisfy their customers. Transformation in Digital transformation starts from an understanding of digital customer behavior. This change must be followed by bankkers both like and dislikes must follow the existing development a The demands of banking are the desire of technology-savvy customers. If the bank does not meet the needs that the customer needs then the customer is ready to leave a bank and switch to bank another Keywords: Islamic bank, digital ecocomy